Aplikasi Analytical Hierarchy Process Pada Pemilihan Metode Analisis Zat Organik Dalam Air - Dino Rimantho; Marrie Rachel; Bambang Cahyadi; Yan Kurniawan (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2016)
Water is one of the food products analyzed in water chemistry and environmental laboratories. One of the parameters analyzed are organic substances. The number of samples that were not comparable with the analytical skills can cause delays in test results. Analytical Hierarchy Process applied to evaluate the analytical methods used. Alternative methods tested include titrimetric method, spectrophotometry, and total organic carbon (TOC). Respondents consisted of deputy technical manager, laboratory coordinator, and two senior analysts. Alternative results obtained are methods of TOC. Proposed improvements alternative analytical method based on the results obtained, the method of the TOC with a 10-15 minute analysis time and use of CRM to the validity of the analysis results.